Foetal Outcome of Complicated Pregnancy in a Tertiary Care Hospital (Journal of Armed Forces Medical College, Bangladesh, 2024)
Background: Neonatal death is responsible for about 45% of the total deaths of children under 5 years of age in Bangladesh. Among the leading causes of neonatal death are infections 36% (sepsis/pneumonia, tetanus and diarrhoea), pre-term birth (28%) and birth asphyxia (23%) which indicates the poor foetal outcome of complicated pregnancy and unhygienic birth process.Objective: To find out the foetal outcome of complicated pregnancy and to minimize foetal death.Methods: An observational study was done purposively on 107 recently delivered women in the Obstetrics and Gynecology Department of Dhaka Medical College Hospital from January 2011 to June 2011. Data were collected by face-to-face interviews of the respondents with a semistructured questionnaire. Verbal consents were taken prior to the interview.Results: Among the newborn baby 93.2% born alive and 6.8% were dead. The association between antenatal complication and birth weight was significant (p